Pre‐loss group therapy for dementia family care partners at risk for complicated grief. Issue 1 (13th May 2021) - Supiano, Katherine P.; Andersen, Troy; Luptak, Marilyn; Beynon, Cynthia; Iacob, Eli; Levitt, Sarah Elizabeth
Abstract: Introduction: Dementia family caregiving may span more than a decade and places many family care partners (CPs) at risk for poor bereavement outcomes; estimates of complicated grief in bereaved dementia family CPs range from 10% to 20%. We adapted our efficacious complicated grief group therapy intervention for bereaved dementia caregivers for soon‐to‐be bereaved dementia CPs at risk for complicated grief to facilitate healthy death preparedness and eventual bereavement—pre‐loss group therapy (PLGT). Methods: In this Stage IB pilot intervention study, we implemented and evaluated PLGT in three psychotherapy group cohorts with family CPs at‐risk for complicated grief whose person living with dementia (PLWD) had a life expectancy of 6 months or less and resided in a nursing home. PLGT is a 10‐session multi‐modal psychotherapy administered by social workers. Results: Participants in PLGT realized significant improvement in their pre‐loss grief and in reported preparedness for the death of their family member, and participants evidenced lowered pre‐loss grief severity and improvement, as measured by facilitators. Participants also realized significant improvement in meaning making, particularly as a sense of peace and a reduction of loneliness. Discussion: The process and treatment elements of the PLGT intervention affirm the value of specialized care for those dementia family CPs at risk for complicated grief, as the PLGT groups demonstrated a steady progression toward improvement collectively and individually. PLGT participants realized statistical and clinical improvement across pre‐loss grief measures suggesting that their risk for complicated grief risk was mitigated, and they were better prepared for the death of their PLWD.